Iris morphologic changes related to alpha(1)-adrenergic receptor antagonists implications for intraoperative floppy iris syndrome - Prata, Tiago Santos; Palmiero, Pat-Michael; Angelilli, Allison; Sbeity, Zaher; De Moraes, Carlos Gustavo V; Liebmann, Jeffrey M; Ritch, Robert (Ophthalmology (Rochester, Minn.), 2009)
To identify iris structural alterations associated with intraoperative floppy iris syndrome (IFIS) in patients using systemic alpha(1)-adrenergic receptor antagonists (alpha-1ARA). Cross-sectional study. Twenty-nine patients with current or past treatment with any systemic alpha-1ARA and 22 untreated controls. Consecutive eligible patients underwent slit-lamp-adapted optical coherence tomography in a masked fashion under standardized lighting conditions. Iris thickness at the dilator muscle region (DMR; measured at half of the distance between the scleral spur and the pupillary margin) and at the sphincter muscle region (SMR; 0.75 mm from the pupillary margin), the ratio between the DMR/SMR (to compensate for possible intersubject variability), and pupillary diameter. Most treated patients were on tamsulosin (27/29). Mean age was similar in study and control groups (70.6+/-7.6 vs 67.1+/-9.1 years; P = 0.061). Photopic pupil diameter was reduced in the study group (2.06+/-0.5 vs 2.5+/-0.6 mm; P = 0.001). The SMR was similar between groups (P = 0.53). Significantly lower values were found in treated subjects for the DMR and the DMR/SMR ratio (P<0.001). These differences remained significant after adjusting for pupil diameter (P<0.001). Multiple regression analysis showed that a longer duration of alpha-1ARA treatment correlated to a reduced DMR/SMR ratio (P = 0.001; r = 0.47). Age and eye color were not significant in this model. Patients using systemic alpha-1ARA have significantly lower values of DMR thickness and DMR/SMR ratio and smaller pupil diameter when compared with age-matched controls. These differences seem to be related to the duration of drug exposure and provide evidence of structural alterations to the iris dilator muscle from this class of agents in IFIS. Proprietary or commercial disclosure may be found after the references.